Confronting the digital mob: Press coverage of online justice seeking. (December 2020) - Trottier, Daniel
This article offers an exploratory account of press coverage of digitally mediated vigilantism. It considers how the UK press renders these events visible in a sustained and meaningful way. News reports and editorials add visibility to these events, and also make them more tangible when integrating content from social media platforms. In doing so, this coverage directs attention to a range of social actors, who may be perceived as responsible for these kinds of developments. In considering how other social actors are presented in relation to digital vigilantism, this study focusses on press accounts of those either initiating or being targeted by online denunciations, and also on a broader and often amorphous range of spectators to such events, often referred to as 'internet mobs'. Relatedly, this article explores how specific practices related to digital vigilantism such as denunciation are expressed in press coverage, as well as coverage of motivations by the public to either participate or facilitate such practices. Reflecting on how the press represent mediated denunciation will illustrate not only how tabloids and broadsheets frame such practices, but also how they take advantage of connective and data-generating affordances associated with social platforms.